Upper Limb Kinematics in Stroke and Healthy Controls Using Target-to-Target Task in Virtual Reality - Hussain, Netha; Alt Murphy, Margit; Sunnerhagen, Katharina S. (Frontiers in Neurology, 2018)
Background: Kinematic analysis using virtual reality (VR) environment provides quantitative assessment of upper limb movements. This technique has rarely been used in evaluating motor function in stroke despite its availability in stroke rehabilitation. Objective: To determine the discriminative validity of VR-based kinematics during target-to-target pointing task in individuals with mild or moderate arm impairment following stroke and in healthy controls. Methods: Sixty-seven participants with moderate (32-57 points) or mild (58-65 points) stroke impairment as assessed with Fugl-Meyer Assessment for Upper Extremity (FMA-UE) were included from the Stroke Arm Longitudinal study at the University of Gothenburg- SALGOT cohort of non-selected individuals within the first year of stroke. The stroke groups and 43 healthy controls performed the target-to-target pointing task, where 32 circular targets appear one after the other and disappear when pointed at by the haptic handheld stylus in a three-dimensional virtual reality environment. The kinematic parameters captured by the stylus included movement time, velocities and smoothness of movement. Results: The movement time, mean velocity and peak velocity were discriminative between groups with moderate and mild stroke impairment and healthy controls. The movement time was longer and mean and peak velocity were lower for individuals with stroke. The number of velocity peaks, representing smoothness, was also discriminative and significantly higher in both stroke groups (mild, moderate) compared to controls. Movement trajectories in stroke more frequently showed clustering (spider’s web) close to the target indicating deficits in movement precision. Conclusion: The target-to-target pointing task can provide valuable and specific information about sensorimotor impairment of the upper limb following stroke that might not be captured using traditional clinical scale. Trial registration details: The trial was registered with register number NCT01115348, on May 4, 2010. URL: https://clinicaltrials.gov/ct2/show/NCT01115348